The Nexus Between High-Involvement Work Practices and Employees’ Proactive Behavior in Public Service Organizations: A Time-Lagged Moderated-Mediation Model - Mehmood K; Iftikhar Y; Khan AN; Kwan HK (Psychology Research and Behavior Management, 2023)
Khalid Mehmood,1 Yaser Iftikhar,2 Ali Nawaz Khan,1 Ho Kwong Kwan3 1Research Center of Hubei Micro & Small Enterprises Development, School of Economics and Management, Hubei Engineering University, Xiaogan, 432100, People’s Republic of China; 2AFPGMI, National University of Medical Sciences, Rawalpindi, 46000, Pakistan; 3Organizational Behavior and Human Resource Management Department, China Europe International Business School (CEIBS), Shanghai, 201206, People’s Republic of ChinaCorrespondence: Ho Kwong Kwan, Organizational Behavior and Human Resource Management Department, China Europe International Business School (CEIBS), Shanghai, 201206, People’s Republic of China, Tel +86-13482520465, Email kwanhokwong@ceibs.edu Ali Nawaz Khan, School of Economics and Management, Hubei Engineering University, Xiaogan, 432000, People’s Republic of China, Tel +86-15695656712, Email alisial@mail.ustc.edu.cnPurpose: Public service organizations may improve the quality of services they offer citizens by instilling proactive behavior in their employees. This study aimed to provide insights on how high-involvement work practices may indirectly facilitate proactive behavior in frontline government employees via employee commitment.Methods: A time-lagged approach was used to collect data from 542 frontline employees in three waves at 3-week intervals. We tested the hypothesized moderated mediation model using a PROCESS macro bootstrap approach.Results: A moderated-meditation model was applied in which public service motivation was theorized to increase the mediating effect of employee commitment on the relationship between high-involvement work practices and employee proactive behavior. As predicted, the findings show that supervisor’ deviant behavior attenuated the mediating effect of employee commitment on the relationship between high-involvement work practices and employee proactive behavior.Conclusion: The findings of this research contribute to the emerging literature on public management and have implications for public sector organizations seeking to improve the quality of services they offer citizens.Keywords: public service motivation, supervisors’ deviant behavior, employee commitment, high-involvement work practices, employee proactive behavior, public sector